Anti-instinctive Learning Behavior Revealed by Locomotion-Triggered Mild Heat Stress in Drosophila - Sun, Ruichen; Delly, Joseph; Sereno, Emily; Wong, Sean; Chen, Xinyu; Wang, Yuxuan; Huang, Yan; Greenspan, Ralph J. (Frontiers in Behavioral Neuroscience, 2020)
Anti-instinctive learning, an ability to modify an animal’s innate behaviors in ways that go against one’s innate tendency, can confer great evolutionary advantages to animals and enable them to better adapt to the changing environment. Yet, our understanding of anti-instinctive learning and its underlying mechanisms is still limited. In this work, we describe a new anti-instinctive learning behavior of fruit flies. This learning paradigm requires the fruit fly to respond to a recurring, aversive, mild heat stress by modifying its innate locomotion behavior. We found that experiencing movement-triggered mild heat stress repeatedly significantly reduced walking activity in wild type fruit flies, indicating that fruit flies are capable of anti-instinctive learning. We also report that such learning ability is reduced in dopamine 1-like receptor 1 (Dop1R1) null mutant and dopamine 2-like receptor (Dop2R) null mutant flies, suggesting that these two dopamine receptors are involved in mediating anti-instinctive learning in flies.